Analysis of the Implementation of the Street Children's Empowerment Program in Improving Social Welfare in the City of Mataram - Syahputra, Aji (JURNAL ILMIAH DETUBUYA, 2025)
This scription discusses the analysis of the implementation of the street children empowerment program in improving social welfare implemented by the Mataram city social service. The effectiveness of this treatment program uses the theory of Ni Wayan Budiani using four indicators of program effectiveness, namely accuracy of program targets, program socialization, implementation of program objectives, and program monitoring. This thesis uses a qualitative and descriptive approach supported by secondary data. Using direct observation and interviews with informants from social services, namely the head of the rehabilitation section and the social rehabilitation task force. Technical data analysis starts from collecting information through interviews and at the final stage with interesting conclusions. The results of the observations show that the program for handling street children implemented by the Mataram city social service is running effectively, because it can be seen that the number of street children in the city of Mataram has decreased every year. However, there are still several things that Mataram city social service officers must pay attention to when dealing with street children. Apart from that, this scription also discusses the steps and programs for handling street children carried out by social services in the city of Mataram. The program in question includes providing food to people who are poor or underprivileged, providing assistive equipment, providing physical, mental, spiritual and social guidance for neglected people with disabilities.